Energy drink consumption among German adolescents: Prevalence, correlates, and predictors of initiation. (1st August 2019) - Galimov, Artur; Hanewinkel, Reiner; Hansen, Julia; Unger, Jennifer B.; Sussman, Steve; Morgenstern, Matthis
Abstract: Background: Energy drinks (EDs) have become popular worldwide. Despite growing concerns about negative health effects of ED, they are increasingly popular among adolescents, yet little is known about the context and patterns of ED use in adolescents. Objective: This study examined the prevalence and correlates of ED use as well as initiation rates and predictors among German adolescents over a one-year period. Design: A school-based longitudinal study of 6902 adolescents ages 9–19 years was conducted in 44 schools in six Federal states of Germany in 2016–2018. Demographics, ED use, drug use behavior, advertising exposure, intrapersonal, interpersonal, and community factors were assessed. Results: Lifetime ED use was reported by 61.7% of the participants, while 21.4% reported past 30-day use. In two multilevel models, lifetime and past 30-day ED use were positively associated with male sex, older age, drug use, poor dietary habits, higher BMI, sensation seeking, worse school performance, and more frequent ad exposure (p < .01). One quarter of the non-users initiated ED use in 12 months. ED initiation was positively associated with male sex (AOR, 1.50 [95% CI, 1.11–2.03]), greater sensation seeking traits (AOR, 1.25 [95% CI, 1.08–1.43]), more frequent ED ad exposure (AOR, 1.31 [95% CI, 1.12–1.53]), and curiosity about trying EDs (AOR, 2.31 [95% CI, 1.74–3.07]), while inversely associated with better school performance (AOR, 0.84, [95% CI, 0.73–0.97]) and attending a gymnasium-type school (AOR, 0.69 [95% CI, 0.50–0.96]). Conclusions: ED consumption is common among German adolescents. The association between EDs and negative health and lifestyle outcomes and risky behaviors is concerning. Parents, school officials, and healthcare providers should be aware of signs and consequences of excessive ED consumption and limit their use by adolescents. Adopting policies that limit the direct marketing to minors under the age of 18 years can be also beneficial in curbing this epidemic.